O acesso à educação superior no discurso mercadológico das instituições privadas - Valle, Bruna Luciana (2025)
This research discusses the policies and strategies that promote access to higher education (SE) in private institutions of higher education (IES) of Mato Grosso do Sul (MS), under the perspective of financialization and market discourse, based on historical-dialectical materialism (MHD). Data from the Census of Higher Education (INEP) and the electronic monitoring system of the processes that regulate Higher Education in Brazil (e-MEC) are used to collect data for the analysis. Also, it is selected the online commercial ads of MS IES in exercise of application of dialogic discourse analysis (ADD). The study has as general objective to analyze the policies and strategies of access to ES in IES of Mato Grosso do Sul, focusing on the effects of financialization and marketing discourse in education, from the perspective of MHD. In order to examine how the marketing discourse influences the strategies of access to private HEIs. It is proposed to identify the implications of financialization in ES, considering the expansion of distance learning (EaD) and investigate as public policies such as Higher Education Student Funding Fund (Fies) and University Program for All (ProUni), strengthen the private sector and impact the emancipatory role of education. The results show the predominance of the private sector in the offer of enrollments, with emphasis on distance learning (EaD), driven by large corporations such as Cogna and Yduqs. These companies use public policies, such as Fies and ProUni, to expand their reach, prioritizing profits over inclusive and emancipatory education. The research argues that, despite the expansion of access, the current model reinforces social inequalities and limits the transformative role of education.